Handbook of Psychology 2003
DOI: 10.1002/0471264385.wei1205
|View full text |Cite
|
Sign up to set email alerts
|

Personnel Selection and Employee Performance

Abstract: This paper is organized around a model of job performance in which personality and ability constructs (KSASOs) are seen as leading to procedural and declarative knowledge and motivation which, in turn, lead to task proficiency and contextual and adaptive behavior. These latter individual performance variables are thought to have implications for a set of distal variables, many of which can be conceptualized as organizational level constructs (e.g., social responsibility and litigation). Our sense is that job a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 265 publications
1
80
0
2
Order By: Relevance
“…Adaptive performance is the proficiency with which a person alters his or her behavior to meet the demands of the environment, an event, or a new situation . Hesketh and Neal (1999), Schmitt, Cortina, Ingerick, and Wiechmann (2003), and Johnson (2003) suggested that adaptive performance is a component of the performance domain that is separate from task and citizenship performance. developed and found support for a taxonomy of adaptive performance consisting of eight dimensions.…”
Section: Adaptive Performancementioning
confidence: 99%
“…Adaptive performance is the proficiency with which a person alters his or her behavior to meet the demands of the environment, an event, or a new situation . Hesketh and Neal (1999), Schmitt, Cortina, Ingerick, and Wiechmann (2003), and Johnson (2003) suggested that adaptive performance is a component of the performance domain that is separate from task and citizenship performance. developed and found support for a taxonomy of adaptive performance consisting of eight dimensions.…”
Section: Adaptive Performancementioning
confidence: 99%
“…The theoretical foundation of this investigation is grounded in the assumption of person-environment (P-E) fit theory. That is, creating perceptions of congruence between individual qualities (e.g., personality traits, interests, abilities) and the inherent characteristics of an occupation or a workplace environment will result in desired work outcomes (e.g., improved performance, higher perceived job satisfaction, tenure) (Assouline & Meir, 1987;Barrick et al, 2003;Edwards, 1996;Kieffer, Schnika, & Curtiss, 2004;Latham & Pinder, 2005;O'Reilly, Chatman, & Caldwell, 1991;Ostroff & Rothausen, 1997;Schneider, 1983;1987;Schmitt, Cortina, Ingerick, & Wiechmann, 2003).…”
Section: The Five-factor Modelmentioning
confidence: 99%
“…Certainly there are some domains where such comparisons are routinely conducted. For example, assessments of differential validity hinge on the ability to make point estimates of the impact of using particular tests for majority and minority candidates (Schmitt, Cortina, Ingerick, & Wiechmann, 2003). Moreover, practitioners are interested in the accuracy of comparisons for gauging the relative utility of interventions or human resource practices.…”
Section: Identical Theoriesmentioning
confidence: 99%